Histological and immunohistochemical characteristics of brain meningiomas - V. A. Byvaltsev (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Meningiomas are among the most common primary intracranial tumors. They arise from meningothelial cells of the arachnoid layer that forms the external lining of the brain and occur primarily at the base of the skull in the parasellar regions as well as over the cerebral convexities. Of particular difficulty are anaplastic meningiomas, having similarities with malignant soft tissue tumors. Immunostaining allows to define not only the source of cytogenetic, tumor grade, but detect abnormal proteins - transcription products damaged DNA regions and make recommendations for the appointment of targeted therapy. Targeted effect on the meningioma will allow to achieve a significant increase in patient survival.